SOCIAL STRENGTHENING OF THE POSITION OF WOMEN AND GIRLS IN SURKHANDARYA REGION AND ITS INITIAL RESULTS (TAMADDUN NURI JURNALI, 2024)
This article describes the participation of women in social and political processes in the Surkhandarya region in the first years of independence.